Narratives of acquired brain injury patients: Their experience of healthcare relationships and medical decision-making. (2nd July 2016) - Wright, M. Michelle; Medved, Maria; Woodgate, Roberta L.; Roger, Kerstin; Sullivan, David
Abstract: Background: Unlike other chronic injuries, acquired brain injuries (ABI's) affect physical, cognitive, social, and emotional functioning. Although collaborative decision-making, high patient engagement, and positive healthcare relationships are generally encouraged within the patient-centred care (PCC) framework, little is known about how ABI patients experience healthcare relationships and decision-making and whether their experiences align with PCC principles. Method: The purpose of this study was to obtain a better understanding of how mild to moderate ABI patients in the chronic phase of recovery (i.e. minimum 2 years post-injury) experience and navigate healthcare using narrative methods. Participants were 11 Canadian adults living in the community and recruited from their local brain injury association. Semi-structured interviews were conducted and analyzed for their thematic content, structural aspects, and performative aspects in order to get at the meaning-making underlying the narrated stories. Findings: These participants told one coherent narrative with two main storylines: one in which they positively portrayed their doctors and their healthcare relationships – reporting feeling lost and needing their doctor's help; and another in which they negatively portrayed their doctors and their healthcare relationships – reporting being capable and therefore not needing their doctor's help. Although seemingly contradictory, these two storylines speak to one coherent experience in which capability served as a counter-narrative to what they perceived as a global narrative of being devalued, dismissed and patronized. Discussion: The implication of how this counter-narrative affects their experience of healthcare is discussed, including implications for why doctors may want to focus on fostering a positive doctor–patient relationship by conveying that they care for and value their ABI patients, and why simple interactions may contribute to this positive relationship.